A comprehensive review of immune checkpoint inhibitor-related diabetes mellitus: incidence, clinical features, management, and prognosis - Zhou, Lin; Yang, Shuhui; Li, Youtao; Xue, Cheng; Wan, Renping (Frontiers in Immunology, 2024)
Immune checkpoint inhibitor-related diabetes mellitus (ICI-DM) is a rare complication that medical oncologists seldom encounter in routine practice. The sporadic nature and intrinsic complexity of ICI-DM make it challenging to analyze comprehensively in experimental settings. In this review, we examine phase 3 clinical trials on ICIs and published case reports of ICI-DM, aiming to summarize its incidence, clinical features, management, and prognosis. Phase 3 clinical trials reveal that the incidence of ICI-DM is higher with combination therapies, such as anti-PD-1 and anti-CTLA-4 or anti-PD-L1, compared to anti-PD-1 monotherapy. ICI-DM typically presents as severe hyperglycemia with a fulminant onset and is often associated with diabetic ketoacidosis, accompanied by unexpectedly low HbA1c and C-peptide levels. ICI-DM shares similarities with classic type 1 diabetes, particularly in terms of autoimmunity and genetic predisposition. This includes a high prevalence of islet autoantibodies and susceptibility to certain HLA haplotypes, often with concurrent endocrine gland dysfunction. This suggests that genetic susceptibility and exposure to ICIs may both be necessary for triggering islet autoimmunity and inducing ICI-DM. Notably, patients with positive islet autoantibodies, such as glutamic acid decarboxylase antibody and islet-associated antigen 2 antibody, tend to experience rapid onset of ICI-DM after ICI exposure. Although patients with ICI-DM generally show a high objective response rate to immunotherapy, a significant proportion also face the need to permanently discontinued treatment. Further research is urgently needed to determine whether permanent discontinuation of immunotherapy is necessary and whether this discontinuation negatively impacts overall survival.